A Diazido Mannose Analogue as a Chemoenzymatic Synthon for Synthesizing Di‐N‐acetyllegionaminic Acid‐Containing Glycosides. Issue 11 (14th February 2018) - Santra, Abhishek; Xiao, An; Yu, Hai; Li, Wanqing; Li, Yanhong; Ngo, Linh; McArthur, John B.; Chen, Xi
Abstract: A chemoenzymatic synthon was designed to expand the scope of the chemoenzymatic synthesis of carbohydrates. The synthon was enzymatically converted into carbohydrate analogues, which were readily derivatized chemically to produce the desired targets. The strategy is demonstrated for the synthesis of glycosides containing 7, 9‐di‐ N ‐acetyllegionaminic acid (Leg5, 7Ac2 ), a bacterial nonulosonic acid (NulO) analogue of sialic acid. A versatile library of α2‐3/6‐linked Leg5, 7Ac2 ‐glycosides was built by using chemically synthesized 2, 4‐diazido‐2, 4, 6‐trideoxymannose as a chemoenzymatic synthon for highly efficient one‐pot multienzyme (OPME) sialylation followed by downstream chemical conversion of the azido groups into acetamido groups. The syntheses required 10 steps from commercially available d ‐fucose and had an overall yield of 34–52 %, thus representing a significant improvement over previous methods. Free Leg5, 7Ac2 monosaccharide was also synthesized by a sialic acid aldolase‐catalyzed reaction. Abstract : Give yourself a Leg up : A library of biologically important α2‐3/6‐linked Leg5, 7NAc2 ‐containing glycosides was built from chemically synthesized 6deoxyMan2, 4diN3 as a chemoenzymatic synthon using one‐pot multienzyme sialylation systems, followed by facile chemical conversion of the azido groups into acetamido groups (see scheme). Commercially available enzymes can be used in this highly efficient chemoenzymatic process.